Problem-Based Learning as a Transformative Framework for Multicultural Education in Secondary Schools - Miranda Wulandari; Jawatir Pardosi; Suryaningsi Suryaningsi (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examines how Problem-Based Learning (PBL) is designed, implemented, and its effectiveness in strengthening multicultural education through the Bhinneka Tunggal Ika topic at SMP Negeri 1 Samarinda. Using a descriptive qualitative case study, the participants comprised one Civic Education teacher and 32 ninth-grade students from class IX F, purposively selected for their religious and ethnic diversity. Data were gathered through participatory observation across five PBL sessions and in-depth interviews, then analyzed using data reduction, data display, and conclusion drawing with source triangulation. The findings show that PBL enhanced students’ multicultural competence, indicated by multicultural knowledge (91%), tolerance for differences (88%), cross-cultural collaboration (84%), and inclusive communication (81%). These gains emerged through five PBL stages: problem orientation, heterogeneous group organization, collaborative investigation, presentation of results, and reflection. The study demonstrates that PBL is an effective transformative approach for cultivating multicultural competence in secondary school civic education, and it offers practical guidance for inclusive, diversity-based teaching in heterogeneous classrooms in a widely diverse context.